THE EFFECT OF WORK ETHICS, HEALTH WORKER PERFORMANCE AND SERVICE QUALITY ON INPATIENT SATISFACTION AT SUMBER HURIP HOSPITAL - Ati Setyowati; Bambang Sumardi; Ellin Herlina (Journal Of Resource Management, Economics And Business, 2025)
Purpose: This study aims to analyze the influence of work ethics, healthcare workers' performance, and service quality on inpatient patient satisfaction at Rumah Sakit Sumber Hurip in Kabupaten Cirebon Research Methodology: This study employs a quantitative approach using surveys and interviews. Data was collected from 50 inpatient patients using a satisfaction questionnaire. The study utilizes tools such as SPSS for data analysis, employing regression analysis to measure the relationship between variables. A review of related literature is included to support the framework. Results: The results indicate that work ethics, healthcare workers' performance, and service quality all have a significant positive impact on inpatient patient satisfaction. Among these, healthcare workers' performance and service quality showed the highest correlation with patient satisfaction. Limitations: The study is limited by the sample size, which only includes 50 patients from a single hospital, and the data collection period, which spans one year. Additionally, the findings may not be generalizable to other regions or hospitals. Contribution: This study contributes to healthcare management by providing insights into the key factors influencing patient satisfaction, which can help improve hospital policies and practices in healthcare settings. The findings are valuable to health management disciplines, hospital administrators, and healthcare professionals.